A comparative study of students’ performance in flipped classroom and structured interactive session teaching learning method in Conservative Dentistry and Endodontics - Shrestha, Sushmita; Vikram, Mannu; Agrawal, Navin; Ayer, Ashok; Shrestha, Ashish (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Flipped classroom is an element of blended learning, integrating both face-to-face learning in the class through group discussion and distance learning outside the class by watching video lessons and online collaboration. The objective of the study was to introduce and assess the effectiveness of flipped classroom in teaching and learning of Conservative Dentistry and Endodontics and to understand the perspective of students about the same.Methods: Third year undergraduate dental students were randomly divided into two groups: structured interactive session group and flipped classroom group. Structured interactive session group had their class taken in the traditional manner while the flipped classroom group was given power point presentation and videos beforehand so that students came to class being prepared. The in class time was utilized for group discussions and peer exercises. Same set of questions including multiple choice questions (MCQs) and problem based questions (PBQs) validated by the faculties involved in the research was used for assessment. A questionnaire was then provided to students regarding their perception of flipped classroom method.Results: Among the 41 students, 19 students were in structured interactive session group and 22 were in flipped classroom group. The mean MCQ and PBQ score in structured interactive session group was 69.47 and 59.39 respectively whereas it was 73.17 and 66.55 respectively in flipped classroom group.Conclusions: The performance of flipped classroom group was better in both MCQs and PBQs. Students preferred flipped classroom method and were ready to accept it as their teaching learning modality.